The Analisis Hubungan Metakognitif Siswa dengan Kemampuan Pemecahan Masalah dalam Pembelajaran Biologi - Yuni Astuti; Nurul Izzah (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Problem Solving is one of the 21st century skills that must be mastered by students. In biology learning, the ability of students to solve problems using their metacognitive skills to process information and knowledge to solve problems. This study aims to describe the relationship between metacognitive skills and problem-solving abilities in biology learning in class XI science. Methods: method used in this research is descriptive correlation. The sampling technique used Cluster Random Sampling with 52 sample. The instrument used in this study was a questionnaire for metacognitive skills as many as 14 statement items with a Likert Scale and an essay test instrument for problem solving abilities as many as 6 questions. The data analysis technique was carried out with the help of the SPSS verse 24 program. Results: of the hypothesis test showed that the value of the correlation coefficient R was 0.123 > 0.05 which means there is no relationship, in the regression equation Y' = 43.6 + 0.245X indicates that the relationship is positive. . In the analysis of variance (F test) the calculated F value was 0.771 with a Significant of 0.384 > 0.05 which means that it is not significant. Conclusions :it can be said that Ha is rejected and Ho is accepted, there is no significant relationship between students' metacognitive skills and problem solving abilities in learning biology. This can be due to the distance learning process that is applied to students related to the outbreak of the Covid-19 virus.